2013
DOI: 10.1042/cs20130117
|View full text |Cite
|
Sign up to set email alerts
|

The composition of cigarette smoke determines inflammatory cell recruitment to the lung in COPD mouse models

Abstract: COPD (chronic obstructive pulmonary disease) is caused by exposure to toxic gases and particles, most often CS (cigarette smoke), leading to emphysema, chronic bronchitis, mucus production and a subsequent decline in lung function. The disease pathogenesis is related to an abnormal CS-induced inflammatory response of the lungs. Similar to active (mainstream) smoking, second hand (sidestream) smoke exposure severely affects respiratory health. These processes can be studied in vivo in models of CS exposure of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 59 publications
6
67
1
Order By: Relevance
“…We found that the total and indirect bilirubin levels in animals exposed to smoke were significantly lower than in control animals. Emphysema was characterized by increased MLI and MAA, and decreased MAN, infiltration of inflammatory cells and secretion of cytokines such as IL-17, TNF-a, CXCL8, CCL2 and CXCL2 [19,20,27,28]. Bilirubin treatment before exposure to smoke ameliorated the smoke-induced reduction in total and indirect bilirubin and attenuated inflammatory cell recruitment and proinflammatory cytokines secretion, increasing anti-inflammatory cytokine IL-10 levels, and augmenting anti-oxidant SOD activity.…”
Section: Discussionmentioning
confidence: 92%
“…We found that the total and indirect bilirubin levels in animals exposed to smoke were significantly lower than in control animals. Emphysema was characterized by increased MLI and MAA, and decreased MAN, infiltration of inflammatory cells and secretion of cytokines such as IL-17, TNF-a, CXCL8, CCL2 and CXCL2 [19,20,27,28]. Bilirubin treatment before exposure to smoke ameliorated the smoke-induced reduction in total and indirect bilirubin and attenuated inflammatory cell recruitment and proinflammatory cytokines secretion, increasing anti-inflammatory cytokine IL-10 levels, and augmenting anti-oxidant SOD activity.…”
Section: Discussionmentioning
confidence: 92%
“…CS was generated from 3R4F Research Cigarettes (Tobacco Research Institute, University of Kentucky, Lexington, KY). Mice were whole body exposed to 100% mainstream CS of 500 mg/m 3 total particulate matter (TPM) for 50 min twice per day for 1, 4, and 6 mo in a manner mimicking natural human smoking habits (24). Control mice were kept in a filtered air (FA) environment, but exposed to the same stress as CS-exposed animals.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the high toxicity of both its gaseous and particle phases (9,47), CS persistently induces a neutrophil and macrophage inflammatory response in the lower respiratory tract of both humans and animals exposed in experimental models (11,24,49). Whereas the acute reaction during the Ϫ⌬⌬Ct values (⌬⌬Ct ϭ ⌬Cttreated Ϫ ⌬Ctcontrol).…”
Section: L700 B Cell Deficiency Protects Against Copdmentioning
confidence: 99%
“…8 B). Typical features of cigarette smoking-associated inflammation are seen in mice after just a few days of cigarette smoke exposure ( John et al, 2014). We exposed C57BL/6 mice to mainstream cigarette smoke from standardized research cigarettes as previously described (Phipps et al, 2010) for 2 h/d for either 3 or 7 d. As compared with smoke-unexposed mice, smoke-exposed mice As demonstrated in BALF from naive mice (Fig.…”
Section: Effects Of Am-derived Socs3 On Pulmonary Stat Activation In mentioning
confidence: 99%